Collins Hotel & Hospitality English - Mike Seymour (Tp. Hồ Chí Minh: Tổng hợp Tp. Hồ Chí Minh ; Công ty Nhân Trí Việt, 2021)
Welcome to the Metro Hotel. Here’s Sarah who works on reception, Simon who is head of Guest Services and David the bartender.